Prolonged static stretching does not influence running economy despite changes in neuromuscular function - Allison, S. J.; Bailey, D. M.; Folland, J. P. (Journal of Sports Sciences, 2008)
The aim of this study was to examine the acute effects of prolonged static stretching (SS) on running economy. Ten male runners (VO2peak 60.1 ± 7.3 ml/kg·min) performed 10 min of treadmill running at 70%VO2peak before and after SS and no stretching interventions. For the stretching intervention, each leg was stretched unilaterally for 40 s with each of eight different exercises and this was repeated three times. Respiratory gas exchange was measured throughout the running exercise with an automated gas analysis system. On a separate day, participants were tested for sit and reach range of motion, isometric strength and countermovement jump height before and after SS. The oxygen uptake, minute ventilation, energy expenditure, respiratory exchange ratio and heart rate responses to running were unaffected by the stretching intervention. This was despite a significant effect of SS on neuromuscular function (sit and reach range of motion, +2.7 ± 0.6 cm; isometric strength, -5.6% ± 3.4%; countermovement jump height -5.5% ± 3.4%; all P < 0.05). The results suggest that prolonged SS does not influence running economy despite changes in neuromuscular function.